Nutrition care in patients with cancer: A retrospective multicenter analysis of current practice – Indications for further studies?. Issue 2 (April 2015) - Drissi, M.; Cwieluch, O.; Lechner, P.; Radziwill, R.; Vehling-Kaiser, U.; Hengst, K.; Masin, M.
Summary Background & aims Weight loss and malnutrition are frequent problems in oncology patients. The aim of this study was to get a perspective of the current practice of parenteral nutrition (PN) care in an outpatient setting and to improve patient-centered nutritional care. Methods Fifty-three outpatient oncology centers participated in this observational study performed between July 2010 and March 2011. All participating centers entered data online into a web-based documentation form, containing a number of oncology patients, diagnoses, and detailed data about oncology patients receiving PN. Results Two cohorts were analyzed. First cohort consisted of all oncology patients in quarter 04/2010. Second cohort consisted of patients with PN during the whole studying period. In the first cohort 2.46% (n = 626) of 25, 424 oncology patients received PN. Most frequent diagnoses of patients receiving PN were gastric cancer (n = 119) and colorectal cancer (n = 104), however most stated diagnosis was "other" (n = 163). In the second cohort (n = 1137), a common indication for PN was impaired gastrointestinal passage (n = 177), although here again most stated reason was "other" (n = 924). In the course of the PN treatment, patients (n = 1137) showed a stable or slowly increasing body mass index (from 21.6 ± 3.8 kg/m2 to 21.8 ± 3.5 kg/m2). Conclusion This is the largest study outlining the characteristics of oncology patients in the context of PN in German ambulatory centers. They confirm the important role of PN in the care of gastrointestinal cancer. Further studies have to be performed to identify if other indications than those mentioned in relevant guidelines can trigger initiation of PN.